2007
DOI: 10.3748/wjg.13.6041
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of serotonin in the jejunum and increased numbers of mast cells in the terminal ileum in patients with irritable bowel syndrome

Abstract: AIM:To investigate if there are changes in serotonin (5-HT) levels, enterochromaffin (EC) cells and mast cells in small intestinal mucosa of patients with irritable bowel syndrome (IBS). n = 20), or constipation-predominant (IBS-C, n = 18) IBS patients and healthy controls (n = 20) underwent colonoscopy and peroral small intestinal endoscopy, and mucosal samples were obtained at the descending part of the duodenum, proximal end of jejunum and terminal ileum. High-performance liquid chromatographyelectrochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
6
29
0
Order By: Relevance
“…For example, Di NArdo et al (2014) demonstrated that the number of mast cells in close proximity to nerves in both ileal and colonic mucosa was increased in IBS children with IBS and were related to the intensity and frequency of abdominal pain (66). In support of this, there are other studies demonstrating small intestinal (jejunum and ileum) involvement in IBS (6769). Therefore, findings presented here in the EWS ileum have relevance to human stress-related GI diseases such as IBS.…”
Section: Discussionsupporting
confidence: 65%
“…For example, Di NArdo et al (2014) demonstrated that the number of mast cells in close proximity to nerves in both ileal and colonic mucosa was increased in IBS children with IBS and were related to the intensity and frequency of abdominal pain (66). In support of this, there are other studies demonstrating small intestinal (jejunum and ileum) involvement in IBS (6769). Therefore, findings presented here in the EWS ileum have relevance to human stress-related GI diseases such as IBS.…”
Section: Discussionsupporting
confidence: 65%
“…The same result was observed in different reptilian species, including in the crocodilians C. latirostris (Yamada et al 1987) and Alligator sinensis (Wu et al 1999); the chelonians M. caspica, T. gracea, L. lepida (Perez-Tomas et al 1989; see also Tarakçi et al 2005 for M. caspica) and Ocadia sinensis (Liu et al 2007); and the squamates E. kingii (Arena et al 1990), C. chalcides, Z. madagascariensis (Morescalchi et al 1997), T. wolteri , G. japonicus, E. chinensis, S. indicus, E. elegans (Huang & Wu 2005), and T. scripta (Zhang & Wu 2009).…”
Section: Intestinesupporting
confidence: 67%
“…This hormone has a strong effect on the regulation of digestive functions (Grundy 2008). The 5-HT could stimulate gastrointestinal mucosa secretion, smooth muscle contraction and the expansion of blood vessels, thus accelerating digestive tract movements (Wang et al 2007). El-Salhy et al (1985) reported that these IR cells are found in the digestive tract of all vertebrate species, a fact that suggests their establishment in this region at an early phase of vertebrate evolution.…”
Section: Intestinementioning
confidence: 99%
“…25,65,100 in serotonin levels in the small intestine and colon of IBS patients, and the expression of 5HT was found to be unaltered in the ileum 65 and the colon. 74,83 Moreover, no region-or symptom-specific patterns could be correlated with these changes, nor have these changes been homogeneously observed across different studies.…”
mentioning
confidence: 88%